The term structure of systematic and idiosyncratic risk - Fabian Hollstein; Marcel Prokopczuk; Chardin Wese Simen (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2017)
We study the term structure of variance (total risk), systematic and idiosyncratic risk. Consistent with the expectations hypothesis, we find that, for the entire market, the slope of the term structure of variance is mainly informative about the path of future variance. Thus, there is little indication of a time-varying term premium. Turning the focus to individual stocks, we cannot reject the expectations hypothesis for the systematic variance, but we strongly reject it for idiosyncratic variance. Our results are robust to jumps and potential statistical biases.
Keywords: G12; G11; G17; 330; Options; term structure; expectations hypothesis; model-free option implied variance; implied correlation; systematic risk; beta; idiosyncratic variance